ENHANCED PARTICIPANTS' REGISTRATION MODEL ON OPEN PUBLIC EVENTS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The Digital transformation (DT) has challenged most of the Event Management (EM) services at a time when organizers of open public events still faced a lot of manual operations upon registration of the public event’s participants. This survey demonstrates a model to increase a level of digitalization and use of technology, with increased self-service level for registered participants and digital data transfer. The model is based on outcomes from the series of several case studies, practical tests and research activities in Latvia, Albania, and Germany. The paper examines different ways how organizers are able to innovate their routine activities and encourage the broader public to learn and use various digital technologies: Radio-frequency identification (RFID), Near-field Communication (NFC), Quick Response (QR) codes and Mobile apps with a purpose to link the physical and the digital world in the one coherent model. In this research the major part of event management process modelling had been done by Business process Model and Notation (BPMN2) approach. The approach proposed by authors aims to reduce the costs and workload of organizers associated with participants’ registration in open public events where preliminary registration is still practically impossible or forbidden because of personal data protection issues.